Fenomena Pernikahan Dini Membuat Orang Tua dan Remaja Tidak Takut Mengalami Kehamilan Tidak Diinginkan - Aprianti Aprianti; Zahroh Shaluhiyah; Antono Suryoputro; Ratih Indraswari (Jurnal Promosi Kesehatan Indonesia, 2018)
Background: In Pati District KTD cases in adolescents aged <17 years as much as 43.8%, which affectsthe marriage at an early age is increasing. This research aims to describe the response of parents and teens junior who experience unwanted pregnancy, and the effects of marriage at an early age.Method: This research method was qualitative case study design. With a purposive sampling and data collection using in-depth interviews. The main informants were adolescent who experienced unwanted pregnancy 5 people. Informants triangulation parents 5 people.Results: The results showed the phenomenon of early marriage makes parents and teens are not afraid of an unwanted pregnancy, as a result people who previously regarded premarital sex behavior that violates norms, are now more likely to be accepted by society. Parents and teenagers who live rural areas provide a response to resolve the problem by marrying unwanted pregnancy informant. While living urban areas, asking informants to have an abortion, but after failing informant eventually wed. Marriage was a solution unwanted pregnancy experienced by adolescents because of the permissive society towards marriage early age and culture in the community who think if the domestic sector only female duties, so that the nature of women is to be a housewife. Suggested provide information to adolescents and parents about the effects of early marriage. The government particularly Health Provider can further provide youthfriendly health services since the junior level.Keywords: unwanted pregnancy, early marriage, adolescents of junior high school